1982
DOI: 10.1111/j.1399-0004.1982.tb01395.x
|View full text |Cite
|
Sign up to set email alerts
|

Hyperphalangy and clinodactyly of the index finger with Pierre Robin anomaly: Catel‐Manzke syndrome. A case report and review of the literature

Abstract: Mandibular hypoplasia, glossoptosis, U‐shaped cleft palate (Pierre Robin anomaly), associated with bilateral index finger malformation and congenital heart disease are described in a male, newborn infant. Review of the features of seven previously published patients, in addition to the patient reported here, confirms the existence of a distinct dysmorphogenesis syndrome. Although all of these eight patients have been males, and most were sporadic, the etiology of this rare malformation syndrome is unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The orthopedic abnormalities are the result of an accessory bone between the second metacarpal and proximal phalanx that causes radial deviation of the second digit (Manzke dysostosis). Cardiac abnormalities, facial dysmorphisms, and additional skeletal abnormalities have also been described in a subset of patients with Catel–Manzke syndrome [3] , [4] , [5] .…”
Section: Introductionmentioning
confidence: 99%
“…The orthopedic abnormalities are the result of an accessory bone between the second metacarpal and proximal phalanx that causes radial deviation of the second digit (Manzke dysostosis). Cardiac abnormalities, facial dysmorphisms, and additional skeletal abnormalities have also been described in a subset of patients with Catel–Manzke syndrome [3] , [4] , [5] .…”
Section: Introductionmentioning
confidence: 99%
“…5 Previously, 26 individuals from 24 families with typical Catel-Manzke syndrome have been reported 2,3,[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] (reviewed by Manzke et al 5 ). Ten cases of an atypical form of Catel-Manzke syndrome have been described, including individuals with an extended phenotype 20,[24][25][26][27][28] and case subjects with unilateral hyperphalangism. 15,29,30 Additionally, two cases of Manzke dysostosis without Pierre Robin sequence have been reported.…”
mentioning
confidence: 99%
“…The family history was negative for cleft palate and skeletal malformations. Since this initial report, authors (Farnsworth & Pacik 1971, Gewitz et al 1978, Holthusen 1972, Silengo et al 1977, Stevenson et al 1980, Sundaram et al 1982 have reported seven additional cases (Table 1). Gorlin et al (1971) mentioned they had "seen another example" of the syndrome but no details were given.…”
Section: Discussionmentioning
confidence: 96%
“…Intellectual development appears to be normal. Chromosome analysis when recorded has been normal (Farnsworth & Pacik 1971, Holthusen 1972, Stevenson et al 1980, Sundaram et al 1982. Dermatoglyphics have been unremarkable.…”
Section: Discussionmentioning
confidence: 99%